Streptococcus Salivarius Subsp Salivarius BIO5 - Toxicity Evaluation of a Possible Probiotic Strain (Global Journal of Medical Research, 2020)
Probiotic bacteria, which are traditionally studied to aid intestinal functions, are also currently being researched for benefits in other parts of the body such as the oral cavity. In the case of throat infections caused by bacteria, which traditional treatment involves antibiotics, some researchers are studying the possibility of introducing special strains of commensal bacteria into the mouth that can specifically inhibit the tonsillitis agent Streptococcus pyogenes for both prevention and treatment of such disease. A PCR assay was used to identify Streptococcus salivarius subsp salivarius. Therefore, tests for the complete absence of toxicity of these strains are required to ensure their safe use in human trials. In this research, we evaluated the new Streptococcus salivarius subsp salivarius BIO5 strain for toxicity factors, as follows: clinical, ophthalmic lesions, behavioral observations, mortality, anatomopathological examination, biopsy, hematology, serum biochemistry, and urine analysis. This strain, isolated from the oral cavity and with bacteriocinogenic activity against S. pyogenes, showed a complete absence of toxicity and thus it may be used in replacement therapy as a probiotic.
Keywords: Streptococcus salivarius; probiotics; bacteriocin; Streptococcus pyogenes; toxicity